ANALISIS PERTUMBUHAN PADA BEBERAPA KERAPATAN TANAM TANAMAN LOBAK (Raphanus sativus L.) - Kalangi, J. I. (Universitas Sam Ratulangi, 2005)
ABSTRACT Kalangi, J.I. 2005. Growth Analysis of Radish Crop (Raphanus Sativus L) Planted in Various Density. Eugenia 11 (1): 18-24. Plant density is known to be important factor to determine the agronomical target of a maximum production. Plant density is generally determined by spacing. The wide spacing, may caused inefficient farm system. On the contrary, narrow by spaced planting can retard growth. Prediction of growth rates and development of crop plants including radish is insufficient if it is relied only on the change that happens to the crop with days after planting. But the basis of the prediction is its potential production biomass. This research is discover the density that suistable for maximum land - use. This research was conducted in a randomized block design, with five density treatments. The treatments were 40 x 60 cm, 45 x 60 cm, 50 x 60 cm, 55 x 60 cm and 60 x 60 cm each of which is repeated three times. The variable obseverved was crop dry matter. Air temperature and rainfall were also recordee. Data were analysed using ANOVA and SSD for mens differences. Radish growth and produces were determined by growth rate (Cm), periode of linear growth (tm) and period of silent growth (to). Plant density significantly affected the growth of radish. The maximum production was found at 50x60 cm with growth rate6.23g m-2 day-1. Keywords: Raphanus sativus, radish growth